Comparative analysis of antibodies to Francisella tularensis antigens during the acute phase of tularemia and eight years later. - Bevanger, L (1994)
Approximately 8 years after treatment for tularemia, 14 of 22 (63.6%) individuals tested still had a positive microagglutination test for Francisella tularensis antibodies. An enzyme-linked immunosorbent assay for anti-F. tularensis outer membrane antibodies was positive for 55% (immunoglobulin A [IgA]), 95% (IgG), and 27% (IgM) of the late-phase sera, but with antibody levels significantly reduced from those in the acute-phase sera. IgG and IgA antibody levels in the late-phase sera showed significant correlation with levels in the acute-phase sera. The IgG/IgM ratio calculation discriminated between acute-phase and persistent antibodies for most sera, but Western blot (immunoblot) patterns did not. Immunoblotting indicated that the F. tularensis lipopolysaccharide is a major target for antibodies in both groups of sera. Our results substantiate the need for caution in the interpretation of positive serological test results for tularemia, which could result from disease occurring years earlier.